Unilateral Termination of Employment for Employees on the Grounds of Company Efficiency: Pemutusan Hubungan Kerja Secara Sepihak Terhadap Pekerja Dengan Alasan Efisiensi Perusahaan - Cendana Suryani; Gunardi Lie (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Employment termination due to corporate efficiency remains a critical issue within Indonesia’s labor framework, as it directly affects workers’ rights and socio-economic stability. Specific Background: Although statutory provisions such as Law No. 13/2003 and its amendments regulate termination, ambiguity persists, particularly regarding the scope of “efficiency,” allowing broad employer discretion. Knowledge Gap: Existing regulations fail to define efficiency clearly and diverge from Constitutional Court rulings requiring permanent business closure, creating inconsistencies in practice. Aims: This study examines the legal basis for efficiency-based termination and identifies corporate considerations in implementing labor efficiency measures. Results: Findings show that recent regulations, particularly PP 35/2021, expand employer flexibility by permitting efficiency-based termination without permanent shutdown, contradicting constitutional standards while increasing risks of unilateral action. Companies must assess internal-external factors, map affected employees, allocate severance budgets, and prepare comprehensive documentation. Novelty: This research highlights the regulatory dissonance between statutory reforms and constitutional jurisprudence while providing a structured framework for lawful termination practices. Implications: Ensuring compliance with legal principles and safeguarding workers’ rights is essential to prevent misuse of efficiency claims and uphold social justice within industrial relations. Highlights: Highlights the legal inconsistency between labor laws and Constitutional Court decisions on efficiency-based termination. Emphasizes the risk of unilateral layoffs due to the vague definition of “efficiency” and “company loss.” Stresses the need for structured corporate procedures to protect workers’ rights and ensure lawful, transparent PHK. Keywords: Termination of Employment, Company Efficiency, Labor Law, Workers’ Rights, Constitutional Conflict